Rehabilitation treatment with jaw reconstruction due to gunshot wound sequela – Case report (Research, Society and Development, 2021)
Introduction: Injuries that affect the maxillofacial complex represent major factors for patients’ health, considering that they are closely associated with aesthetic defects, decreased or loss of function, and morbidities. For jaw fractures due to gunshot wounds (GSW), treatment can be immediate or delayed, and may or may not involve reconstruction and rehabilitation. Purpose: To report a clinical case of mandibular reconstruction with subsequent dental rehabilitation in a patient suffering from GSW injuries. Methodology: The work was traditionally carried out for a case study as a research strategy. Case Report: Patient with sequela caused by jaw fracture due to a GSW 7 years ago, presenting facial asymmetry, deviation of the mandibular midline, alteration of occlusion, and absence of dental elements. Imaging examination, confirming the fracture of the right mandibular body with loss of bone segment. The proposed and performed treatment consisted of a bone graft, with the iliac crest as a donor area, applied between the fracture lines, and subsequent rehabilitation through implants. Discussion: The treatment for mandibular reconstruction still lacks an established consensus, it being the responsibility of the surgeon in charge to clinically consider each case. The iliac crest graft is one of the possibilities for treatment, mainly because the gain in thickness and mandibular height is of great importance in oral rehabilitation with dental implants, which is the ultimate goal in mandibular reconstruction. Conclusion: Through the exposed case and after a current literature review, it can be concluded that the main purpose of the treatment has been achieved.